Computational Analysis of Interactions Between Drugs and Human Serum Albumin - Yildiz, Muslum (Wiley, 2024)
Drug molecules exist as complexed with serum proteins such as human serum albumin (HSA) and/or unbound free form in the blood circulation. Drugs can be effective only when they are free. Thus, it is important to understand aspects that are important for interaction between drugs and interacting proteins. In this study, interactions among 2990 FDA approved drugs and HSA were computational analyzed to unravel principles that are critical for drug-HSA interactions. Docking results showed that drugs have higher affinity toward cavity-1 (C1) than cavity-2 (C2). A total of 1131 drug molecules have docking score greater than 60 while 768 molecules have docking score greater than 60 when they are docked in C2. In addition, three solvent channels have potential to direct solvent to C1 cavity while C2 does not have any effective channel. The post MD analyses demonstrated that drugs are making polar interactions with basic amino acids in the binding cavities. Verbscoside and ceftazidime both have stable low RMSD values throughout MD simulation with 2 & Aring; on average in C1 cavity. The ligand RMSD shows less stability for verbscoside, which is around 4 & Aring; when it is in complex with HSA in C1. The individual contribution of the residues K192, K196, R215, and R254 to ceftazidime are -1.92 +/- 0.18, -3.09 +/- 0.09, -2.17 +/- 0.17, and - 2.32 +/- 0.098, respectively. These residues contribute the binding energy of the verbscoside by -6.06 +/- 0.08, -2.10 +/- 0.06, and - 1.57 +/- 0.03 kcal/mol individually in C1 cavity. C2 is making polar interactions with drug via R469, K472, and K488 residues and their contribution to the two drugs are -3.13 +/- 0.21 kcal/mol for R469, -1.94 +/- 0.18 kcal/mol for K472, and -1.96 +/- 0.11 kcal/mol for K488 to total binding energy of ceftazidime. The binding energy of verbscoside is 57.17 +/- 7.00 kcal/mol and Arg-407 has the highest contribution this bind energy individually with -4.29 +/- 0.12 kcal/mol. Drugs with hydrogen bond donor/acceptor chemical adducts such as verbscoside involve higher hydrogen bond formation in C1 pocket. Ceftazidime makes interaction with HSA toward hydrophobic residues, L384, L404, L487, and L488 in the C2 cavity.
Keywords: albumin; docking; drug interaction; < fixed-case > HSA